Respostas
respondido por:
1
NUMERADOR
a⁻² = 1/a²
b⁻² = 1/b²
DENOMINADOR
a⁻¹ = 1/a¹
b⁻¹ = 1/b¹
armando a conta
( 1/a² - 1/b²)/ ( 1/a + 1/b) =
fatorando o primeiro parenteses ( soma pela diferença)
( 1/a + 1/b)( 1/a - 1/b) / ( 1/a + 1/b)
cortando 1/a + 1/b) temos
1/a - 1/b
mmc = ab
( b - a)/ab ****** ( c )
a⁻² = 1/a²
b⁻² = 1/b²
DENOMINADOR
a⁻¹ = 1/a¹
b⁻¹ = 1/b¹
armando a conta
( 1/a² - 1/b²)/ ( 1/a + 1/b) =
fatorando o primeiro parenteses ( soma pela diferença)
( 1/a + 1/b)( 1/a - 1/b) / ( 1/a + 1/b)
cortando 1/a + 1/b) temos
1/a - 1/b
mmc = ab
( b - a)/ab ****** ( c )
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás